ANTARA PELUANG DAN ANCAMAN: PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PROSES PRODUKSI BERITA MEDIA LOKAL DI KOTA SURAKARTA - Hastjarjo, Sri; Dewi, Sabila Soraya (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2025)
The development of artificial intelligence (AI) technology has significantly impacted journalistic practices, including at the local level. This study explores the perceptions of journalists in Surakarta City regarding the benefits, challenges, and ethical implications of AI use in news production. Using a qualitative case study approach, data were collected through in-depth interviews with five journalists from various media platforms. The findings reveal that journalists view AI as a supporting tool that accelerates work processes and enhances production efficiency. However, concerns about the degradation of information quality and potential violations of journalistic ethics remain critical issues. AI acceptance is influenced by perceived usefulness, ease of use, and the professionalism values upheld by journalists. This study recommends strengthening digital literacy and updating journalistic ethical regulations to address the challenges of media transformation in the era of artificial intelligence.